Exhaust gas emissions in daihatsu granmax vehicles based on the year of manufacture - Fikri Setiawan; Ali Akbar; Mulyadi (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
Air pollution is a condition caused by exhaust gas from motorized vehicles operating on the highway. To minimize greater air pollution, the government is making preventive efforts by carrying out periodic vehicle emission tests which are currently being carried out. carry out transport targeting vehicles. The research aims to determine the year of the vehicle that produces the dominant CO (carbon monoxide) and HC (hydrocarbon) exhaust emissions which were tested based on vehicle year from 2017 to 2022, with the type of gasoline-fueled vehicle, in this case the Daihatsu granmax. The method used is experimental using Manova analysis of 30 samples used with variations in data taken from testing CO and HC exhaust emissions on 30 samples with 5 vehicles each in each year of production. The results of the research that has been carried out show that the emission test results on sample data show the highest CO exhaust emissions in vehicles in 2017 and the lowest in vehicles in 2021, while the HC test results in vehicles in 2017 are the highest and continue to decline to the lowest point in vehicles in 2022, this provides a conclusion: Vehicles produced longer have the potential to produce high exhaust emissions, while vehicles produced younger do not cause exhaust emissions